Identifying Light Pollution Sources at Two Major Observatories in Malaysia - Tahar, Mohammad R.; Ahmad, Nazhatulshima; Ismail, Nur H. (Penerbit Universiti Kebangsaan Malaysia, 2020)
A spectral observation and analysis were conducted in order to identify the main contributor of sky brightness at two of Malaysia’s most active observatories. The light pollution observations were carried out under moonless clear night sky with a 90 mm refractor telescope and SBIG’s Self Guiding Spectrograph. We found that the main contributor to Balai Cerap Teluk Kemang (BCTK) sky brightness is High Pressure Sodium (HPS) street lighting due to its number and density used within 5 km radius of the observatory. HPS spectral lines dominate the spectrum between 556 - 640 nm, agrees with the orange hue visible to the naked eye. The intensity due to HPS lighting is so high that there was no trace of the concerned white LED spotlight less than 1 km away. However, some traces of elements from Mercury Vapor (MV) lamps at 3.6 km distance managed to reach the observatory in the green spectrum. The finding concludes that the nearby LED spotlight does not affect the night sky brightness over BCTK. Meanwhile, Langkawi National Observatory (LNO) sky profile was also observed during heavy fishing season as comparison. The sky spectra for LNO was similar to BCTK in the reds except for a very distinct peak in green region corresponding highly with green MV (532 - 547 nm) with peaks at 536 nm and 546 nm, matches the lamps used for squid fishing around the island. The intensity of the green MV light matches the intensity of HPS light sources, during the observation period of peak squid season in January. This made LNO a far less favorable condition for astronomical observing site compared to BCTK. We also found that LNO sky has brightened 3.767 times compared to finding of 2013. © 2020 Penerbit Universiti Kebangsaan Malaysia. All rights reserved.